Implementation of Medical Record Application for Patient Registration Data Management at Pagar Jati Health Center - Ginting, Darmanto; Purba, Rini Armaida; Octavariny, Raisha (JURNAL PENGMAS KESTRA (JPK), 2024)
advancement in health services that help improve the quality of health systems worldwide, including Indonesia. Electronic Medical Records (EMR) applications have been useful for improving the efficiency and quality of health services in the health industry. The use of medical applications is a global trend, and electronic medical records are believed to be able to improve the quality of health information services. Improving access and quality of patient services is very important for health organizations such as health centers, so data management is an important solution in improving efficiency. The development of the Medical Record Application at Pagar Jati School is a high priority initiative that aims to provide a system that is capable of handling patient data. Based on the findings of the health center accreditation process in 2016, the service of raw materials, both in-hospital and out-of-hospital raw materials, has been implemented in accordance with the health center supply management standards. The use of information systems is encouraged to improve efficiency. This includes documentation of patient symptoms and the speed of treatment delivery, as well as the accuracy of information obtained from patient registration to initial treatment. To ensure that all anticipated goals and outcomes are achieved, direct monitoring and support will be used in the final stage to evaluate each step of the work process. The Medical Record Application is expected to increase the efficiency of administrative data processing in terms of speed and accuracy of the data produced as well as reduce operational costs, minimizing the possibility of data loss and damage.